Fructose-1,6-bisphosphatase deficiency as a cause of recurrent hypoglycemia and metabolic acidosis: Clinical and molecular findings in Malaysian patients - Lip Hen Moey; Nor Azimah Abdul Azize; Yusnita Yakob; Huey Yin Leong; Wee Teik Keng; Bee Chin Chen; Lock Hock Ngu (Elsevier, 2018)
Background: Fructose-1,6-bisphosphatase (FBPase) deficiency is a rare autosomal recessive inborn error of gluconeogenesis. We reported the clinical findings and molecular genetic data in seven Malaysian patients with FBPase deficiency. Methods: All patients diagnosed with FBPase deficiency from 2010 to 2015 were included in this study. Their clinical and laboratory data were collected retrospectively. Results: All the patients presented with recurrent episodes of hypoglycemia, metabolic acidosis, hyperlactacidemia and hepatomegaly. All of them had the first metabolic decompensation prior to 2 years old. The common triggering factors were vomiting and infection. Biallelic mutations in FBP1 gene (MIM*611570) were identified in all seven patients confirming the diagnosis of FBPase deficiency. In four patients, genetic study was prompted by detection of glycerol or glycerol-3-phosphate in urine organic acids analysis. One patient also had pseudo-hypertriglyceridemia. Seven different mutations were identified in FBP1, among them four mutations were new: three point deletions (c.392delT, c.603delG and c.704delC) and one splice site mutation (c.568-2A > C). All four new mutations were predicted to be damaging by in silico analysis. One patient presented in the neonatal period and succumbed due to sepsis and multi-organ failure. Among six survivors (current age ranged from 4 to 27 years), four have normal growth and cognitive development. One patient had short stature and another had neurological deficit following status epilepticus due to profound hypoglycemia. Conclusion: FBPase deficiency needs to be considered in any children with recurrent hypoglycemia and metabolic acidosis. Our study expands the spectrum of FBP1 gene mutations. Key Words: Fructose-1,6-bisphosphatase, FBPase deficiency, FBP1 gene mutation